Impacto da suplementação com colecalciferol na calcificação vascular e pressão arterial de pacientes com doença renal crônica e hipovitaminose D - Samaan, Farid [UNIFESP] (2018)
Background: The role of nutritional vitamin D in vascular calcification and hypertension in chronic kidney disease (CKD) has not been established. The objective of this randomized double-blind trial was to evaluate the impact of long-term supplementation with cholecalciferol in the progression of coronary artery calcification (CAC) and blood pressure of CKD stages 3-4 patients with hypovitaminosis D. Methods: Sixty-eight patients with creatinine clearance between 15 and 60mL/min/1.73m² and serum 25-hydroxyvitamin D [25(OH)D]<30ng/mL were recruited. Individuals with vitamin D deficiency [25(OH)D≤15ng/mL] received cholecalciferol (50,000IU/week for 12 weeks and adjusted thereafter), whereas those with vitamin D insufficiency [25(OH)D between 16 and 29ng/mL] were randomized to placebo or cholecalciferol group (50,000IU/month). Multislice computed tomography to estimate calcium score and 24-hour ambulatory BP monitoring (ABPM) were performed at baseline and after 18 months. Biochemical parameters were also analyzed. Results: In the deficient group there was a significant increase in 25(OH)D levels (11±2 to 43±15ng/mL; p<0.001) while vascular calcification progressed [265(84-733) to 333(157- 745)AU; p=0.006] and renal function declined [35(26-43) to 23(17-49)mL/min/1.73m²; p=0.04]. Of note, calcium score change was inversely correlated with kidney function change (r= -0.43; p=0.03) and cholecalciferol cumulative doses (r= -0.41; p=0.048) but not with vitamin D levels change. In the treated insufficient group there was a significant increase in 25(OH)D levels (20±3 to 38±9; p=<0.001) while vascular calcification and renal function did not change [418(109-918) to 364(232-817)AU, p=0.25 and 35(27-44) to 37(29- 48)mL/min/1.73m², p=0.25; respectively]. In the placebo insufficient group there was a significant increase in 25(OH)D levels (22±4 to 30±9ng/mL; p<0.001) and calcium score [118(37-421) to 199(49-490)AU; p=0.01], while no change in the kidney function was observed [31(26-41) to 41(20-48); p=0.36]. In the treated insufficient group, but not in the placebo, calcium score change was inversely correlated with 25(OH)D change (r= -0.45; p=0.037). In a multivariate analysis, there was no difference in CAC progression between insufficient treated and placebo groups (interaction p=0.92). ABPM parameters did not change among the three groups during the study.